Two-Photon Na+ Imaging Reports Somatically Evoked Action Potentials in Rat Olfactory Bulb Mitral and Granule Cell Neurites - Ona-Jodar, Tiffany; Gerkau, Niklas J.; Sara Aghvami, S.; Rose, Christine R.; Egger, Veronica (Frontiers in Cellular Neuroscience, 2017)
Dendrodendritic synaptic interactions are a hallmark of neuronal processing in the vertebrate olfactory bulb. Many classes of olfactory bulb neurons including the principal mitral cells (MCs) and the axonless granule cells (GCs) dispose of highly efficient propagation of action potentials (AP) within their dendrites, from where they can release transmitter onto each other. So far, backpropagation in GC dendrites has been investigated indirectly via Ca2+ imaging. Here, we used two-photon Na+ imaging to directly report opening of voltage-gated sodium channels due to AP propagation in both cell types. To this end, neurons in acute slices from juvenile rat bulbs were filled with 1 mM SBFI via whole-cell patch-clamp. Calibration of SBFI signals revealed that a change in fluorescence ∆F/F by 10% corresponded to a ∆[Na+]i of ~ 22 mM. We then imaged proximal axon segments of MCs during somatically-evoked APs (sAP). While single sAPs were detectable in ~ 50% of axons, trains of 20 sAPs at 50 Hz always resulted in substantial ∆F/F of ~ 15% (~ 33 mM ∆[Na+]i). ∆F/F was significantly larger for 80 Hz vs 50 Hz trains, and decayed with half-durations τ1/2 ~ 0.6 s for both frequencies. In MC lateral dendrites, AP trains yielded small ∆F/F of ~ 3% (~ 7 mM ∆[Na+]i). In GC apical dendrites and adjacent spines, single sAPs were not detectable. Trains resulted in an average dendritic ∆F/F of 7% (16 mM ∆[Na+]i) with τ1/2 ~ 1 s, similar for 50 Hz and 80 Hz. Na+ transients were indistinguishable between large GC spines and their adjacent dendrites. Cell-wise analysis revealed two classes of GCs with the first showing a decrease in ∆F/F along the dendrite with distance from the soma and the second an increase. These classes were clustering with morphological parameters. Simulations of ∆[Na+]i replicated these behaviors via negative and positive gradients in Na+ current density, assuming faithful AP backpropagation. Such specializations of dendritic excitability might confer specific temporal processing capabilities to bulbar principal cell-GC subnetworks. In conclusion, we show that Na+ imaging provides a valuable tool for characterizing AP invasion of MC axons and GC dendrites and spines.